The Effectiveness of Canva-Based Animated Video Media in Pancasila Education Learning: The Bhinneka Tunggal Ika Element fot Grade V Elementary School Students - Reinita; Mira Maulidya Fajar (Jurnal Pedagogi dan Pembelajaran, 2026)
The limited use of innovative instructional media in Pancasila Education has reduced students’ learning engagement and hindered their understanding of the values of Bhinneka Tunggal Ika. Conventional teacher-centered learning practices often fail to provide meaningful and interactive learning experiences, resulting in less optimal learning outcomes in elementary schools. This study aimed to examine the effectiveness of Canva-based animated video media in improving students’ learning outcomes in the Bhinneka Tunggal Ika element of Pancasila Education. The study employed a Research and Development (R&D) approach using the ADDIE model, consisting of the analysis, design, development, implementation, and evaluation stages. The research involved 68 fifth-grade elementary school students, who participated in limited trials, implementation, and dissemination stages. Data were collected through pretest and posttest learning achievement tests and analyzed using the normalized gain (N-Gain) method to evaluate learning improvement after the implementation of the developed media. The findings indicate that the Canva-based animated video media produced a moderate and sufficiently effective improvement in students’ learning outcomes across all stages of implementation. The interactive visual presentation, animation, and contextual learning content also enhanced students’ engagement and participation throughout the learning process. These findings suggest that Canva-based animated video media represents an effective instructional innovation for strengthening students’ understanding of Pancasila values while promoting more engaging, meaningful, and student-centered learning in elementary education.